1998
DOI: 10.1016/s0735-1097(98)00057-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of Acute Rest Technetium-99m Tetrofosmin Tomographic Myocardial Perfusion Imaging in Patients With Acute Chest Pain and Nondiagnostic Electrocardiograms

Abstract: Abnormal rest Tc-99m tetrofosmin SPECT imaging accurately predicts acute MI in patients with symptoms and a nondiagnostic ECG, whereas a normal study is associated with a very low cardiac event rate. The use of acute rest SPECT imaging in the ED can substantially and safely reduce the number of unnecessary hospital admissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
0
6

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(94 citation statements)
references
References 35 publications
4
84
0
6
Order By: Relevance
“…19 -25 However, there is room for improvement. In a cohort of 357 patients imaged acutely as part of an ED triage protocol, Heller et al 24 reported normal images at rest in 12 of 35 patients (34%) who ultimately were diagnosed with ACS, including 2 with acute MI. Normal images were acquired in 7 of 32 patients with ACS (22%) in a cohort of Ͼ1000 patients with chest pain.…”
Section: Discussionmentioning
confidence: 99%
“…19 -25 However, there is room for improvement. In a cohort of 357 patients imaged acutely as part of an ED triage protocol, Heller et al 24 reported normal images at rest in 12 of 35 patients (34%) who ultimately were diagnosed with ACS, including 2 with acute MI. Normal images were acquired in 7 of 32 patients with ACS (22%) in a cohort of Ͼ1000 patients with chest pain.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal rest MPI in patients with acute chest pain is highly associated with acute myocardial infarction or the need for subsequent coronary revascularization [2]. These images demonstrate the exquisite sensitivity of MPI to changes in rest myocardial perfusion over a short period.…”
mentioning
confidence: 88%
“…Contemporary studies confirmed the high negative predictive value (99%) of rest MPI for excluding ACS. [10][11][12] However, the radiopharmaceutical must be injected during ongoing chest pain or within 6 hours after chest discomfort has abated, for optimal results. If rest MPI is normal in a patients with acute chest pain, the likelihood of ACS is extremely low and the 30-day outcome is very favorable.…”
Section: Rest Myocardial Perfusion Imaging (Mpi)mentioning
confidence: 99%
“…If rest MPI is normal in a patients with acute chest pain, the likelihood of ACS is extremely low and the 30-day outcome is very favorable. 10 In reality, very few patients evaluated in CPCs still have ongoing chest pain. Rest MPI is therefore rarely performed.…”
Section: Rest Myocardial Perfusion Imaging (Mpi)mentioning
confidence: 99%